Perception of general health and self-efficacy for the coronary artery bypass graft patient - Schaffer, Sandra (My University, 2009)
The purpose of this study was to examine the relationship between perception of general health and self-efficacy in the coronary artery bypass graft (CABG) patient. Following CABG, risk factor modification and adoption of new health behaviors can be difficult. Because self-efficacy is strongly related to behavioral intentions and behavioral change, understanding what factors impact self-efficacy is important. The research question for this study was: What is the relationship between perception of general health and self-efficacy in the CABG patient? The theoretical framework for this study is Bandura's Social Cognitive Theory. Self-efficacy is a key element of the Social Cognitive Theory where emphasis is placed on the beliefs about abilities to execute an action rather than the skills possessed. A non-experimental, ex post factor, correlational design was used to conduct this study. A non-probability, convenience sample consisted of 776 adults who had undergone CABG theory and participated in a cardiac rehabilitation program in Wisconsin. Data collection instruments used were: (a) W2eBOP Individual Patient Outcomes-Phase II, (b) Short-Form 36-ltem Health Survey, and (c) Modified Cardiac Self-Efficacy Tool. Data were analyzed using Pearson's r and descriptive statistics. Alpha was set at .05. This study demonstrated a highly statistically significant relationship between pretest general health (GH) and posttest self-efficacy controlling symptoms (SE-CS) (r = .289 [p < .000)). Even after age, pre SE-CS and gender were controlled for, the relationship between variables remained statistically significant (r = .1283 [p < .000]). In this sample of 776 CABG patients, a highly significant relationship was demonstrated between pre GH and post SE-CS. By providing expert medical care. individualized health education and positive feedback regarding health status, the advanced practice nurse is in a key position to help positively influence GH for the CABG patient. As the GH increases, the SE-CS increases and better quality of life is obtained for the CABG patient. Referrals to cardiac rehabilitation should be included in the care of all CABG patients and new interventions to enhance GH should be pursued.
A Clinical Paper Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Nursing - Family Nurse Practitioner -- University of Wisconsin-Oshkosh, 2008
Keywords: Health Knowledge, Self-efficacy; Coronary artery bypass, Patients, Rehabilitation; Heart Disease, Health behavior